„Staroświeccy mieszczanie”. Intymistyka Michała Głowińskiego w perspektywie kulturowej - Okupnik, Małgorzata (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
Michał Głowiński is the author of autobiographical series including: Czarne sezony, Magdalenka z razowego chleba, Kładka nad czasem, Historia jednej topoli and Kręgi obcości. His works may be analysed in a number of different ways. One of them is to take a view of middle-class values, frequently presented in his autobiographical stories. As Głowiński writes, he comes from a middle-class Jewish family and his grandparents were merchants, the ones in Victorian middle-class style. Głowiński’s stories contribute greatly to a literary documentation of those forever lost people and times; those real ‘old-fashioned townspeople’.